Virtual Embodiment of White People in a Black Virtual Body Leads to a Sustained Reduction in Their Implicit Racial Bias - Banakou, Domna; Hanumanthu, Parasuram D.; Slater, Mel (Frontiers in Human Neuroscience, 2016)
Virtual reality can be used to visually substitute a person’s body by a life-sized virtual one. Such embodiment results in a perceptual illusion of body ownership over the virtual body (VB). Previous research has shown that the form of the VB can influence implicit attitudes. In particular, embodying White people in a Black virtual body is associated with an immediate decrease in their implicit racial bias against Black people. We tested whether the reduction in implicit bias lasts for at least one week and whether it is enhanced by multiple exposures. Two experiments were carried out with a total of 90 female participants where the virtual body was either Black or White. Participants were required to follow a virtual Tai Chi teacher who was either Asian or European Caucasian. Each participant had 1, 2 or 3 exposures separated by days. Implicit racial bias was measured one week before their first exposure and one week after their last. The results show that implicit bias decreased more for those with the Black virtual body than the White. There was also some evidence of a general decrease in bias independently of body type for which possible explanations are put forward.